Linear groups saturated by subgroups of finite central dimension - Semko, N.N.; Skaskiv, L.V.; Yarovaya, O.A. (Reports of the National Academy of Sciences of Ukraine, 2019)
Let F be a field, A be a vector space over F, and G be a subgroup of GL(F, A). We say that G has a dense family of subgroups having finite central dimension, if, for every pair of subgroups H, K of G such that H ≤ K and H is not maximal in K, there exists a subgroup L of finite central dimension such that H ≤ L ≤ K (we can note that L can match with one of the subgroups H or K). We study locally solvable linear groups with a dense family of subgroups having finite central dimension.